Policy Diffusion on New and Renewable Energy in Indonesia - Mendrofa, Andika Sefatia; Sugandi, Yogi Suprayogi; Rusli, Budiman; Amalia, Prita (Journal of Ecohumanism, 2024)
This research emphasizes the need for a specific legal framework to harmonize new and renewable energy (NRE) policies in Indonesia, as current efforts to develop and implement NRE have been slow. By exploring policy diffusion, this study aims to offer solutions for accelerating NRE usage through relevant policies. Using a qualitative approach, it examines four policy diffusion mechanisms from Ring’s framework: (i) learning, (ii) competition, (iii) imitation, and (iv) coercion. The 2015 Paris Agreement, which Indonesia ratified in 2016, plays a key role in diffusing NRE policies, especially through coercive mechanisms.The study’s findings suggest that (i) the Paris Agreement’s global benchmarks provide a basis for Indonesia to adopt a learning mechanism, using insights from other countries that have met their NDCs; (ii) the competition mechanism could help Indonesia attract funding from developed countries by positioning itself as a viable candidate for climate aid; (iii) through imitation, Indonesia can adopt successful NRE policies from other countries, adapting them to local needs; and (iv) coercive mechanisms require Indonesia, as a Paris Agreement signatory, to enforce NRE policies aligned with international climate goals. The research concludes that Indonesia should integrate all four policy diffusion mechanisms into its NRE strategy and advocates for a specific NRE law. This law would unify related regulations, align policies with international standards, attract investment, and support Indonesia’s NRE goals under the Paris Agreement.